Makna Anak Laki – laki dalam Budaya Tionghoa Berdasarkan Tinjauan Nilai Dasar Insani - Catherine Stephanie; Listyo Yuwanto (EduInovasi: Journal of Basic Educational Studies, 2025)
presence of a son in a Chinese family is seen as more valuable because there is a certain value in a son. This literature research aims to analyze and explain the meaning of boys in terms of basic human values. This research is included in cultural psychology research. The results of this literature study show that there are 8 values ​​for boys, including: traditional values, security, conformity, benevolence, prosperity, appreciation, strength, and stimulation. Referring to the results of literature research, a psychological approach can be applied in developing knowledge, understanding and insight about the meaning of boys in various cultures.